Association of generalized anxiety symptoms and panic with health care costs in older age: results from the ESTHER cohort study - Hohls, Johanna Katharina; Wild, Beate; Brenner, Hermann; Böhlen, Friederike; Saum, Kai-Uwe; Schöttker, Ben; Haefeli, Walter E. (Journal of affective disorders, 2019)
Background - Little is known specifically about the association between generalized anxiety symptoms or panic and health care costs in older age. The aim of this study was to examine the association between generalized anxiety symptoms, panic and health care costs in people aged 65 and over. - Methods - Cross-sectional data from the 8-year follow-up of a large, prospective cohort study, the ESTHER study, was used. Individuals aged 65 and over, who participated in the study's home assessment, were included in this analysis (n=2348). Total and sectoral costs were analyzed as a function of either anxiety symptoms, probable panic disorder, or a panic attack, while controlling for selected covariates, using Two Part and Generalized Linear Models. Covariates were chosen based on Andersen's Behavioral Model of Health Care Use. - Results - There was no significant association between either of the anxiety or panic measures and total health care costs. Stratified by health care sectors, only the occurrence of a panic attack was significantly associated with incurring costs for outpatient non-physician services (OR: 1.99; 95% CI: 1.15-3.45) and inpatient services (OR: 2.14; 95% CI: 1.07-4.28). Other illness-related factors, such as comorbidities and depressive symptoms, were associated with health care costs in several models. - Limitations - This was a cross-sectional study relying on self-reported data. - Conclusion - This study points to an association between a panic attack and sector-specific health care costs in people aged 65 and over. Further research, especially using longitudinal data, is needed.
Gesehen am 20.12.2018
Available online: 13 November 2018